The Effect of Anaerobic Exercises on Some Physical Abilities in 50m Freestyle for Young Swimmers - Gafoor , Tara; Najemaldeen , Eman (Journal of Physical Education, 2023)
The research aimed at identifying the effect of anaerobic exercises on some physical abilities of young swimmers in 50m freestyle. The researchers used the experimental method on (6) swimmers with average highest, weight, and ages 171.17+2.86 cm), (65.67+5.75 kgm), (13.17+0.75) years respectively. Arm and legs explosive power tests were conducted as well as strength – speed tests for arms and legs and Stamina 4×50m test. The training program was applied with (80 – 90%) intensity consisting of (24) training session for (8) weeks with (3) training session per week. The time for executing these exercises took (15 – 20) minutes to reach the results. The data was collected and treated using SPSS to conclude significant differences between pre and posttests in favor of the posttests in the variables of the study.